Herbicides: How Toxic Are They? - Jason Ferrell; Frederick Fishel; Cody Gray; Greg MacDonald; Curtis Rainbolt; Brent Sellers (EDIS)
Although there have been pesticides that are toxic and dangerous to handle, most of these products are no longer used and have been replaced by newer chemistry. PI-133, a 3-page fact sheet by Jason Ferrell, Fred Fishel, Cody Gray, Greg MacDonald, Curtis Rainbolt, and Brent Sellers, describes how the toxicity of chemicals is documented, and explains why herbicides are often less toxic than many commonly used household products. Includes sources for additional information and a table listing toxicity values for common herbicides in comparison with common consumer chemicals. Published by the UF Pesticide Information Office, September 2006.